Pengaruh Cita Rasa dan Fasilitas Pelayanan Terhadap Kepuasan Pelanggan Pada Restoran Guang Wei Yuan - Esteria Febriati Hutagalung; Ananda Fitriani Dewi (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2025)
Customer satisfaction is the level of a person's feelings after comparing the perceived performance (or results) compared to their expectations. To be able to do something more valuable, it is not enough to just provide service, but must be able to provide satisfaction to customers. The population of this study were customers who purchased food from Guang Wei Yuan Restaurant in Medan City. The sampling technique where the population size is unknown, the researcher used the Lameshow formula. Therefore, the minimum number of samples needed in this study is 96 respondents which will be rounded by the researcher to 100 respondents. The significance value of the results is 0.000 which is smaller than 0.05. This indicates that hypothesis 1 in this study is accepted, which means that taste has a significant influence on Customer Satisfaction while the significance value of the results is 0.002 which is smaller than 0.05. This indicates that hypothesis 2 in this study is accepted, which means that service facilities have a significant influence on Customer Satisfaction, then the significance value of the results is 0.000 which is smaller than 0.05. This shows that in this study it was accepted, which means that taste and service facilities simultaneously have a significant influence on customer satisfaction.